Safety and Immunogenicity of a PHH-1V Booster Dose after Different Prime Vaccination Schemes against Covid-19: Phase III Clinical Trial Final Results Up To One Year - Martínez, Silvina Natalini; Ramos, Rafael; Navarro-Perez, Jorge; Lopez, Maria Jesus; Vazquez, Maria del Mar; Molto, Jose; Munoz, Patricia; Echave, Jose M; Arribas, Jose R; Alvarez, Melchor; et al. (Archives of Clinical and Biomedical Research, 2024)
In this phase III, open-label, single-arm, multicenter clinical study we report on the safety, tolerability and immunogenicity of PHH-1V as a booster dose in subjects primary vaccinated against COVID-19 with the BNT162b2, mRNA-1273, ChAdOx1-S, or Ad26.COV2.S vaccines, with or without previous COVID-19 infection. A total of 2661 subjects were included in the study and vaccinated with the PHH-1V vaccine. Most treatment-emergent adverse events (TEAEs) were solicited local and systemic reactions of grade 1 (58.70%) or grade 2 (27.58%) intensity - the most frequently reported problems being injection site pain (82.83%), fatigue (31.72%) and headache (31.23%). Additionally, immunogenicity was assessed at baseline and on days 14, 91, 182 and 365 in a subset of 235 primary vaccinated subjects. On day 14, the geometric mean titer (GMT) of neutralizing antibody against SARS-CoV-2 Wuhan and Beta, Delta and Omicron BA.1 variants increased in all primary vaccination subjects, with a geometric mean fold rise (GMFR) of 6.90 (95% CI 4.96-9.58), 12.27 (95% CI 8.52-17.67), 7.24 (95% CI 5.06-10.37) and 17.51 (95% CI 12.28-24.97), respectively. Despite GMT decay after day 14, the titers in all cases remained significantly higher versus baseline for up to one year after PHH-1V booster administration, with GMFR against Beta and Omicron BA.1 variants of over 3 at one year after booster compared to baseline. PHH- 1V booster vaccination also elicited significant RBD/ spike-specific IFN-γ+ T-cell responses on day 14. Overall, PHH-1V vaccine was immunogenic and well-tolerated regardless of the previous primary vaccination scheme received, with no reported cases of severe COVID-19 infection throughout the entire study.